Positron Emission Tomography in the Neuroimaging of Autism Spectrum Disorder: A Review - Tan, Zhiqiang; Wei, Huiyi; Song, Xiubao; Mai, Wangxiang; Yan, Jiajian; Ye, Weijian; Ling, Xueying; Hou, Lu; Zhang, Shaojuan; Yan, Sen; Xu, Hao; Wang, Lu (Frontiers in Neuroscience, 2022)
Autism spectrum disorder (ASD) is a pervasive developmental disease characterized by persistent impairment, repetitive and stereotypical behaviors during social interactions, as well as restricted interests and activities. The etiology of ASD is currently unclear, which results in difficulties in clinical diagnosis and treatment, increasing the burden to patients and society. Positron emission tomography (PET) is a molecular imaging technology that can be utilized in vivo for dynamic and quantitative research, and is a valuable tool for exploring pathophysiological mechanisms, evaluating therapeutic efficacy, and accelerating drug development in ASD. Recently, several imaging studies on ASD have been published and physiological changes during ASD progression was disclosed by PET. This paper reviews the specific radioligands for PET imaging of critical biomarkers in ASD, and summarizes and discusses the similar and different discoveries in outcomes of previous studies. It is of great importance to identify general physiological changes in cerebral glucose metabolism, cerebral blood flow perfusion, abnormalities in neurotransmitter systems, and inflammation in the central nervous system in ASD, which may provide excellent points for further ASD research.